352 Skeletal muscle transcriptional profiling of Canadian crossbred beef cattle divergent for feed efficiency traits. (7th December 2018) - Mukiibi, R; Vinsky, M; Keogh, K; Fitzsimmons, C; Waters, S; Stothard, P; Li, C
Abstract: In beef cattle, skeletal muscle tissue represents a large energy sink within the animal, accounting for over 60% of the animal's systemic metabolism. Therefore, identifying the differentially expressed (DE) genes between the muscle tissues of beef cattle with divergent feed intake and growth rate would enhance our understanding of the molecular mechanisms that regulate feed efficiency in beef cattle. Using RNAseq analyses we investigated transcriptome expression differences of Gluteus medias muscle tissues between crossbred steers with divergent residual feed intake (RFI), daily dry matter intake (DMI), or average daily gain (ADG). For each of these traits, RNAseq data of six (n=6) Kinsella Composite (KC) steers with extreme high and six (n=6) with extreme low phenotypes were analyzed to identify DE genes. On average, we obtained 26.4 million reads per sample with an average quality score of 36, and 97.5% were of the desired length (90-101bp) with 92% of the reads uniquely mapped to the bovine reference genome (UMD3.1). At a false discovery rate < 0.05 and fold change > 2, we identified 271, 383, and 22 DE genes between RFI, ADG, and DMI divergent steers, respectively. Of the identified DE genes, 17 ( TFRC, AFF4, NBEAL1, PHIP, NFAT5, HSPA6, FRAS1, HSPA1A, UHMK1, KMT2A, HOOK3, KLHL24, SMG1, ZBED6, RPL12, ROCK2 and ENSBTAG00000017233 ) were common among the three traits, of which 16 DE genes except for RPL12 were downregulated in steers of low phenotypic values for all the traits. The DE genes between the steers divergent in RFI were primarily involved in gene expression regulation, cellular development, cellular growth and proliferation, cellular function and maintenance and carbohydrate metabolism. Results from this study provide insight into the molecular control of skeletal muscle tissue contributing to divergence in feed efficiency potential in beef cattle.